2022
DOI: 10.1002/smtd.202200420
|View full text |Cite
|
Sign up to set email alerts
|

Breaking with the Principles of Coreduction to Form Stoichiometric Intermetallic PdCu Nanoparticles

Abstract: surface sites. Each metal has a specific binding affinity toward the adsorbates involved in each catalytic reaction, which allows for selective tuning and optimization of catalytic processes via consideration of the incorporated metals. [1] In a binary disordered alloy, two metals randomly occupy symmetry equivalent sites in the crystal lattice, while the metals in an intermetallic structure occupy the crystallographic sites in the structure in a nonrandom arrangement at a specific atomic stoichiometry. [2] Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…In addition, an oleylamine reaction system consisting of metal acetylacetonates, FeCl 3 , and AA was used for directly synthesizing ordered PdCu intermetallic nanoparticles . The growth mechanism of PdCu intermetallics under such synthesis conditions was further clarified using in situ X-ray total scattering and pair distribution function analysis . They found that the successful synthesis required both additives capable of reoxidation of Fe 3+ ↔ Fe 2+ and fast and continuous reducing agents.…”
Section: Synthetic Strategies Of Intermetallicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, an oleylamine reaction system consisting of metal acetylacetonates, FeCl 3 , and AA was used for directly synthesizing ordered PdCu intermetallic nanoparticles . The growth mechanism of PdCu intermetallics under such synthesis conditions was further clarified using in situ X-ray total scattering and pair distribution function analysis . They found that the successful synthesis required both additives capable of reoxidation of Fe 3+ ↔ Fe 2+ and fast and continuous reducing agents.…”
Section: Synthetic Strategies Of Intermetallicsmentioning
confidence: 99%
“…286 The growth mechanism of PdCu intermetallics under such synthesis conditions was further clarified using in situ X-ray total scattering and pair distribution function analysis. 287 They found that the successful synthesis required both additives capable of reoxidation of Fe 3+ ↔ Fe 2+ and fast and continuous reducing agents. Specifically, Fe 3+ was first reduced into Fe 2+ to oxidatively etch preformed Cu-rich seeds to form metal ions (M + ), and then the AA was oxidized into dehydroascorbic acid to dampen the reduction rate of metal ions.…”
Section: Surface Ligand-assistedmentioning
confidence: 99%
“…Metal halides are commonly used for synthesis of bi-and intermetallic NPs. 17,28 Firstly, it is well-known that halide ions (e.g. Cl − , Br − ) can modify reduction kinetics and the atom diffusion/ exchange rate by coordinating with metal ions during the synthesis of metallic NPs.…”
Section: Inuence Of Metal Precursor Saltmentioning
confidence: 99%
“…The reaction does thus not take place through the conventional Bain transformation, which we have previously observed for PdCu. 17 Instead, the PdIn particles may…”
Section: In Situ Studies Of Pdin Nanoparticle Formation: Inuence Of Oamentioning
confidence: 99%
“…Other reactors exist, as reviewed by Jensen et al (2014), and the various reactors have different strengths including probing at the mixing point of a mixing-flow reactor (Beauvais et al, 2022). Alternative approaches include employing nuclear magnetic resonance tubes with a larger diameter of 3 mm, such as in a recent study of PdCu 3 formation (Mathiesen et al, 2022).…”
Section: Introductionmentioning
confidence: 99%